toner
By incorporating specific organosilicon and titanium acid compound fine particles into toner particles, the issues of charging instability and development performance at higher speeds are addressed, resulting in stable and high-quality toner performance.
Patent Information
- Application Number
- JP2023179288
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-05-01
AI Technical Summary
Existing toners with round-shaped external additives suffer from burial and localization on the toner surface when subjected to strong stress, leading to unstable charging properties and deteriorated development performance, especially at higher speeds.
The use of toner particles containing a binder resin, organosilicon compound fine particles (A) with specific Si-NMR characteristics, and titanium acid compound fine particles (B) with controlled circularity and particle size ratio, which together enhance charge stability and development performance.
The proposed solution achieves excellent charging stability and high development performance even during long-term image output, effectively preventing particle burial and localization.
Smart Images

Figure 2025069522000007 
Figure 2025069522000001 
Figure 2025069522000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner used in electrophotography, electrostatic recording, and the like. [Background technology]
[0002] In recent years, full-color electrophotographic copying machines have become widespread and are beginning to be applied to the printing market, where there is a growing demand for high speed, high image quality, and high stability. To achieve high and stable image quality, it is necessary to stabilize the charging characteristics of the toner. In order to stabilize the charging characteristics of the toner, various external additives have been investigated. Conventionally, silica has been widely known as an external additive used in toners. In general, examples have been reported in which silica obtained by a dry or wet method (sol-gel method) has been subjected to a surface treatment to enhance hydrophobicity. For example, Patent Document 1 describes an example in which highly hydrophobic spherical sol-gel silica microparticles are added to toner base particles to improve the charging stability of the toner. Patent Document 2 describes an example in which polyalkylsilsesquioxane microparticles are added to toner base particles to improve the fluidity and charging stability of the toner. On the other hand, Patent Document 3 discloses a toner in which the number-average particle size of primary particles is 10 nm or more and 95 nm or less, and charging stability is improved by externally adding strontium titanate having a specific value for the half-value width of the diffraction angle in X-ray diffraction. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-99582 A [Patent Document 2] Patent No. 6116711 [Patent Document 3] Patent Publication No. 2022-22414 Summary of the Invention [Problem to be solved by the invention]
[0004] However, when strong stress is applied to the toner due to the increase in speed, it was found that the round-shaped external additives as in Patent Documents 1 and 2 are embedded in the toner surface or localized. As a result, it was found that the chargeability of the toner changes and the developability deteriorates. In addition, Patent Document 3 also has room for improvement in order to increase the speed. An object of the present invention is to provide a toner that solves the above problems, specifically, to provide a toner that has charging stability and can maintain good developability even when images are output over a long period of time. [Means for solving the problem]
[0005] The present invention relates to a toner having toner particles containing a binder resin, fine particles A which are organosilicon compounds having siloxane bonds, and fine particles B, The fine particles A 29 In a chart obtained by Si-NMR measurement, when the total peak area attributable to silicon polymers is SA and the peak area attributable to Si-R1 bonds (R1 represents an alkyl group having 1 to 6 carbon atoms) is SB, the following formula (1) is satisfied: 0.26≦SB / SA≦0.45 (1) The toner is characterized in that the fine particles B are a titanate compound, the average circularity of the primary particles of the fine particles B is 0.700 or more and 0.920 or less, and the ratio AD / BD of the number average particle diameter of the primary particles of the fine particles A and the fine particles B satisfies the following formula: 1.0≦AD / BD≦10.0 Effect of the Invention
[0006] According to the present invention, it is possible to provide a toner that has good charging stability and high developability even when images are output over a long period of time. [Brief description of the drawings]
[0007] [Figure 1]FIG. 2 is a schematic explanatory diagram of a heat treatment device used in a heat treatment step, which is suitable for controlling the adhesion rate of organosilicon compound fine particles to toner particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In the present invention, the descriptions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limits which are the endpoints, unless otherwise specified. In addition, the toner according to the present invention has toner particles and an external toner additive, and in the following description, "toner particles" may be referred to as "toner mother particles" or "toner mother".
[0009] [Features of the present invention] The inventors have investigated toners that can provide high image quality and high stability even at even higher speeds, and have found that by using a toner having the configuration of the present invention and having externally added organosilicon compound microparticles and titanic acid compound microparticles, it is possible to suppress changes in the surface condition of the toner, maintain good charging stability over the long term, and maintain high developability.
[0010] The present inventors consider the mechanism by which the effects of the present invention are manifested as follows.
[0011] In order to prevent the toner from being embedded in the toner surface, fine particles A, which are an organosilicon compound, are added externally. 29 In a chart obtained by Si-NMR measurement, when the total peak area attributable to silicon polymers is defined as SA and the peak area attributable to the Si-R1 bond (R1 represents an alkyl group having 1 to 6 carbon atoms) is defined as SB, it is necessary that the following formula (1) is satisfied. 0.26≦SB / SA≦0.45 (1)
[0012] However, such organosilicon compound particles have low adhesion to the toner matrix, and when the toner is subjected to stress, such as contact with a charging member, the particles tend to roll and localize in the recesses on the surface of the toner matrix, which changes the charge of the toner and reduces the developability.
[0013] As a result of extensive research into improving the charge stability of the toner, the inventors have found that by externally adding the fine particles A together with the fine particles B, which are the titanate compound of the present invention, embedding of the fine particles in the toner matrix and localization due to rolling can be suppressed, thereby improving the charge stability of the toner and improving the developability.
[0014] The average circularity of the primary particles of the fine particles B of the present invention is 0.700 or more and 0.920 or less. The average circularity of the primary particles is 0.700 or more and 0.920 or less, which means that the particles are non-spherical. In addition, the ratio AD / BD of the number average particle size of the primary particles of the fine particles A and the fine particles B must satisfy the following formula. 1.0≦AD / BD≦10.0
[0015] With this structure, the titanate compound particles penetrate between the organosilicon compound particles on the toner surface, generating an anchor effect and suppressing localization due to rolling. In addition, the structures of particle A and particle B generate electrostatic adhesion, improving the adhesion to the toner base particles.
[0016] [External additives] The configuration and manufacturing method of the external additive according to the present invention will be described in detail below.
[0017] <Fine particles A> The fine particles A, which are organosilicon compounds of the present invention, are 29 In a chart obtained by Si-NMR measurement, when the total peak area attributable to silicon polymers is defined as SA and the peak area attributable to the Si-R1 bond (R1 represents an alkyl group having 1 to 6 carbon atoms) is defined as SB, the compound is characterized in that it satisfies the following formula (1): 0.26≦SB / SA≦0.45 (1)
[0018] 29 In Si-NMR, peaks are detected in different shift regions depending on the structure of the functional group that bonds to the Si of the constituent compounds of the organosilicon compound fine particles. The structure that bonds to the Si can be identified by identifying the position of each peak using a standard sample. In addition, the abundance ratio of each constituent compound can be calculated from the obtained peak area.
[0019] The ratio of the peak area of the M unit structure (S1 below), the D unit structure (S2 below), the T unit structure (S3 below), and the Q unit structure (S4 below) to the total peak area can be calculated.
[0020] [ka] (Ra, Rb, Rc, Rd, Re, and Rf each represent an alkyl group having 1 to 6 carbon atoms.)
[0021] 29 The ratio of the area derived from Si-R1 (R1 represents an alkyl group having 1 to 6 carbon atoms) to the total peak area measured by Si-NMR is the abundance ratio of Si-R1 inside the external additive particle. By satisfying the following formula (1), the amount of alkyl groups present inside the external additive particle becomes optimal, which can suppress embedding in the toner mother particle and improve charging stability. 0.26≦SB / SA≦0.45 (1)
[0022] If SB / SA is less than 0.26, the amount of alkyl groups present inside the particles is too small, and the effect of the present invention is not achieved. If SB / SA is more than 0.45, the amount of siloxane bonds present inside the particles is relatively small, and the robustness and stability of the particles are reduced.
[0023] A more preferable range is 0.28≦SB / SA≦0.45, and a further preferable range is 0.30≦SB / SA≦0.40, since the charge stability of the toner is further improved.
[0024] The method for producing the organosilicon compound microparticles of the present invention is not particularly limited, but it is preferable to form particles through hydrolysis of silane monomers by the sol-gel method and condensation polymerization reaction. Specifically, particles are formed by polymerizing a mixture of a bifunctional monomer (above S2) having two siloxane bonds and a tetrafunctional monomer (above S4) having four siloxane bonds through hydrolysis and condensation polymerization reaction. In the production method, the present inventors have prepared organosilicon compound microparticles that exhibit the above effects by adjusting the mixing ratio of the monomers, the solvent temperature during the hydrolysis and condensation reaction, the type of catalyst, the stirring time, and the pH of the solution. The tetrafunctional monomer used in the present invention can be appropriately selected depending on the hydrolysis property with the solvent, but is preferably tetraethoxysilane. In addition, the bifunctional monomer is preferably dimethyldimethoxysilane.
[0025] The number average particle diameter of the primary particles of the organosilicon compound fine particles of the present invention is preferably 0.02 μm or more and 0.30 μm or less. When the number average particle diameter of the primary particles is within the above range, the fine particles can be uniformly coated on the toner particles. In addition, the stress on the toner can be suppressed, so that the effect of charge stability is easily obtained. When the number average particle diameter of the primary particles of the organosilicon compound fine particles is less than 0.02 μm, when a large amount of images with low print density are output for a long time under a harsh environment such as a high temperature and high humidity environment, the stress on the toner increases, so that the fine particles may be easily buried in the toner surface. In addition, when the number average particle diameter of the primary particles of the organosilicon compound fine particles exceeds 0.30 μm, the fine particles may be easily detached from the toner surface.
[0026] From the above viewpoint, the number average diameter of the primary particles of the organosilicon compound fine particles is more preferably from 0.05 μm to 0.25 μm, and even more preferably from 0.08 μm to 0.18 μm.
[0027] The organic silicon compound fine particles of the present invention are preferably surface-treated with a hydrophobizing agent. The hydrophobizing agent is not particularly limited, but is preferably an organic silicon compound. For example, alkylsilazane compounds such as hexamethyldisilazane, alkylalkoxysilane compounds such as diethyldiethoxysilane, trimethylmethoxysilane, methyltrimethoxysilane, butyltrimethoxysilane, and octamethylcyclotetrasiloxane, chlorosilane compounds such as dimethyldichlorosilane and trimethylchlorosilane, or silicone oil and silicone varnish can be mentioned. By hydrophobizing the surface of the external additive particles, the change in the charge amount of the toner in a high-temperature and high-humidity environment can be further suppressed. Among these, it is preferable that the particles are treated with at least one compound selected from the group consisting of alkylsilazane, alkylalkoxysilane, chlorosilane, and silicone oil. Furthermore, it is more preferable to treat the particles with alkylsilazane in terms of environmental stability and charge stability.
[0028] The organosilicon compound fine particles of the present invention are 29 In a chart obtained by Si-NMR measurement, when the total peak area attributable to silicon polymers is SA, the peak area attributable to Q unit structures is S4, the peak area attributable to T unit structures is S3, and the peak area attributable to D unit structures is S2, 0.20≦S4 / SA≦0.60, 0≦S3 / SA≦0.50, 0.20≦S2 / SA≦0.70 It is preferable to satisfy the above. When the toner is subjected to stress from a charging member or the like, the embedding of the fine particles in the toner particle surface and the destruction of the fine particles themselves can be suppressed. Furthermore, when 0.30≦S4 / SA≦0.50, 0≦S3 / SA≦0.10, and 0.50≦S2 / SA≦0.70, the ratio of the amount of Si-CH3 and the amount of silanol groups present inside the fine particles becomes optimal, which is more preferable from the viewpoint of the charging stability of the toner.
[0029] The content of the organosilicon compound fine particles of the present invention in the toner base particles is preferably 0.1 parts by mass or more and 20.0 parts by mass or less, more preferably 0.5 parts by mass or more and 15.0 parts by mass or less, and even more preferably 1.0 parts by mass or more and 10.0 parts by mass or less, based on 100 parts by mass of the toner base particles, from the viewpoint of charging stability.
[0030] If the content of the organosilicon compound microparticles is less than 0.1 parts by mass, when a large amount of images with low print density are output over a long period of time, the stress on the toner cannot be suppressed, and it becomes difficult to obtain the effect of improving the durability and charging stability.
[0031] Furthermore, if the content of the organosilicon compound particles exceeds 20.0 parts by mass, when an image with high print density is output for a long period of time, filming of the external additive particles onto the carrier or photosensitive member may occur.
[0032] <Fine particles B> On the other hand, the fine particles B, which are titanic acid compounds in the present invention, must have an average circularity of primary particles of 0.700 or more and 0.920 or less in order to exhibit the anchoring effect. The average circularity of the fine particles B is preferably 0.750 or more and 0.870 or less, more preferably 0.800 or more and 0.850 or less. By controlling the average circularity within the above range, the anchoring effect can be further enhanced, and the charging stability of the toner is improved.
[0033] The number average particle diameter of the primary particles of the fine particles B is preferably 0.01 μm or more and 0.10 μm or less. More preferably, it is 0.01 μm or more and 0.05 μm or less. By controlling the number average particle diameter within the above range, the anchor effect can be further enhanced, thereby improving the charging stability of the toner. The circularity and number average particle diameter of the primary particles of the fine particles B can be controlled by the concentration of the raw materials, the reaction temperature, and the reaction time.
[0034] The titanic acid compound particles of the present invention preferably have a dielectric constant of 10 pF / m or more and 40 pF / m or less at 2 MHz. Titanic acid compound particles having a dielectric constant within the above range are preferable because they improve the charging stability of the toner. In addition to the selection of titanic acid compound particles, methods for controlling the dielectric constant include conditions / operations for changing the particle crystallinity when producing titanic acid compound particles, such as changing the reaction temperature or water pressure in the case of a dry method, or changing the pH or temperature in the case of a wet method, or performing ultrasonic treatment or bubbling treatment during crystallization. More preferably, the dielectric constant is 20 pF / m or more and 35 pF / m or less. Even more preferably, the dielectric constant is 25 pF / m or more and 35 pF / m or less.
[0035] Examples of the titanate compound fine particles that can be used include potassium titanate, barium titanate, strontium titanate, calcium titanate, magnesium titanate, lead titanate, aluminum titanate, lithium titanate, etc. Strontium titanate is particularly preferred for obtaining the effect of charge stability.
[0036] Titanic acid compound microparticles are preferably surface-treated with a compound having an alkyl group, because the interaction with organosilicon compound microparticles enhances the effect of suppressing localization.That is, the treatment agent can be unmodified silicone varnish, various modified silicone varnishes, unmodified silicone oil, various modified silicone oil, silane coupling agent, silane compound having functional group, or other organosilicon compound.Various treatment agents can be used in combination.Among these, it is particularly preferable to treat with a silane coupling agent.That is, it is preferable that titanic acid compound microparticles are surface-treated microparticles with a silane coupling agent.
[0037] Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyltrimethoxysilane, and phenyltrimethoxysilane. Examples of the silane include phenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, trimethylmethoxysilane, n-hexyltrimethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, hydroxypropyltrimethoxysilane, n-hexadecyltrimethoxysilane, n-octadecyltrimethoxysilane, trifluoropropyltrimethoxysilane, and hydrolysates thereof.
[0038] Among these, n-octyltriethoxysilane, isobutyltrimethoxysilane, and trifluoropropyltrimethoxysilane are preferred, and isobutyltrimethoxysilane is more preferred. These treating agents may be used alone or in combination of two or more.
[0039] The titanate compound fine particles may be doped with a metal element other than the elements constituting the titanate. The metal element to be doped is not particularly limited, but examples thereof include lanthanum, silicon, aluminum, magnesium, calcium, manganese, rhodium, ruthenium, iridium, tantalum, chromium, antimony, nickel, rhodium, and niobium. Among these, lanthanum is preferred in terms of controlling the circularity.
[0040] There is no particular restriction on the method for preparing the titanic acid compound fine particles, but for example, strontium titanate can be produced by the following method. Strontium nitrate, strontium chloride, etc. are added to a titania sol dispersion obtained by adjusting the pH of a titanium oxide hydrous slurry obtained by hydrolyzing a titanyl sulfate aqueous solution, and the mixture is heated to a reaction temperature, after which an alkaline aqueous solution is added to synthesize the titanic acid compound fine particles. The reaction temperature is preferably 60 to 100°C.
[0041] In order to control the number average particle size and circularity of the primary particles, the time taken for adding the alkaline aqueous solution in the step of adding the alkaline aqueous solution is preferably 60 minutes or less. Furthermore, in order to control the circularity, it is preferable to add the alkaline aqueous solution while applying ultrasonic vibration in the step of adding the alkaline aqueous solution.
[0042] In addition, in order to control the primary particle size and circularity, it is preferable to add an aqueous alkali solution to the aqueous solution after the reaction is completed and then rapidly cool it. As a method for rapid cooling, for example, a method of adding pure water cooled to 10°C or less until the temperature reaches a desired level can be mentioned. By rapid cooling, the circularity can be controlled to be high in the cooling process.
[0043] <Relationship between particle size and amount of added particles A and B> In the present invention, the number average particle diameter AD of the organosilicon compound fine particles A, relative to the number average particle diameter BD of the primary particles of the titanic acid compound fine particles B, must satisfy the following formula: 1.0≦AD / BD≦10.0
[0044] Within the above range, it is possible to exert the anchoring effect of the fine particles B to the fine particles A and the effect of suppressing embedding of the fine particles B in the toner matrix. Furthermore, it is preferable that 2.0≦AD / BD≦6.0 because the above effects are further enhanced.
[0045] In addition, the toner of the present invention preferably satisfies the following formula, where the amount of organosilicon compound fine particles A added is X and the amount of titanic acid compound fine particles B added is Y, relative to 100 parts by mass of toner particles. 0.7≦X / Y≦3.0
[0046] When X / Y is within the above range, it is preferable for improving the charging stability of the toner. Preferably, 1.0≦X / Y≦2.5. More preferably, 1.5≦X / Y≦2.5.
[0047] [Toner Particles] Next, the constitution of the toner particles to which the above-mentioned external additive fine particles of the present invention are externally added will be described in detail.
[0048] <Binding resin> The binder resin used in the toner of the present invention is not particularly limited, and the following polymers or resins can be used.
[0049] For example, homopolymers of styrene and its substitutes such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-α-methyl chloromethacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, and styrene-acrylonitrile-indene copolymer are usable as styrene-based copolymers; polyvinyl chloride, phenolic resin, naturally modified phenolic resin, naturally modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, and petroleum-based resin can be used. Among them, polyester resin is preferred from the viewpoint of durability and electrostatic stability.
[0050] In addition, the acid value of the polyester resin is preferably 0.5 mgKOH / g or more and 40 mgKOH / g or less from the viewpoint of environmental stability and charging stability. The acid value in the polyester resin and Si-CH3 in the external additive interact with each other to further improve the toner charging property in a high humidity environment. The acid value is more preferably 1 mgKOH / g or more and 20 mgKOH / g or less, and even more preferably 1 mgKOH / g or more and 15 mgKOH / g or less.
[0051] <Crystalline polyester> The toner of the present invention preferably contains a crystalline polyester, and more preferably contains a crystalline polyester containing a monomer having a linear hydrocarbon chain having 8 to 12 carbon atoms.
[0052] As monomers having a linear hydrocarbon chain with 8 to 12 carbon atoms, the following alcohol components can be mentioned (the number of C's listed indicates the number of carbon atoms in the linear hydrocarbon chain): 1,8-octanediol (C8), 1,9-nonanediol (C9), 1,10-decanediol (C10), 1,11-undecanediol (C11), and 1,12-dodecanediol (C12).
[0053] Carboxylic acid components include the following (the numbers indicate the number of carbon atoms in the linear hydrocarbon chain): sebacic acid (C8), 1,9-nonanedicarboxylic acid (C9), 1,10-decanedicarboxylic acid (C10), and 1,12-dodecanedicarboxylic acid (C12).
[0054] In the present invention, the crystalline polyester preferably contains the above-mentioned monomer component having a linear hydrocarbon chain in an amount of 40 mol % or more.
[0055] Examples of the other monomer components contained in the crystalline polyester include the following.
[0056] Examples of the alcohol component include aromatic diols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,20-icosanediol, polyoxypropylene adducts of 2,2-bis(4-hydroxyphenyl)propane, and alkylene oxide adducts of bisphenol A including polyoxyethylene adducts of 2,2-bis(4-hydroxyphenyl)propane; glycerin, pentaerythritol, and trimethylolpropane.
[0057] Examples of the carboxylic acid component include oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc. Further examples include anhydrides of these acids and lower alkyl esters of these acids. Examples of the alkyl group in the lower alkyl esters include methyl, ethyl, propyl, and isopropyl groups.
[0058] Among these combinations of components, from the viewpoint of low-temperature fixability and image storage stability, a crystalline polyester containing 40 mol% or more of 1,10-decanedicarboxylic acid is preferred. More preferably, a crystalline polyester containing 40 mol% or more of 1,10-decanedicarboxylic acid and 40 mol% or more of 1,6-hexanediol is preferred. By using a crystalline polyester with such a composition, it is possible to increase the affinity between the toner base particles and the organosilicon compound particles, suppress localization of the organosilicon compound particles, and improve the charging stability of the toner.
[0059] The weight average molecular weight of crystalline polyester is 1.0×10 4 Above 1.0×10 5 It is preferable that the value is less than 2.0×10 4 Above 5.0×10 4The melting point of the crystalline polyester is preferably 60° C. or higher and 85° C. or lower, and more preferably 62° C. or higher and 73° C. or lower.
[0060] When the weight average molecular weight and melting point of the crystalline polyester are within the above ranges, the charge stability of the toner becomes better.
[0061] <Coloring agent> The toner of the present invention may contain a colorant, if necessary. Examples of the colorant include the following.
[0062] Examples of black colorants include carbon black, and a mixture of a yellow colorant, a magenta colorant, and a cyan colorant toned to black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of the image quality of a full-color image.
[0063] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0064] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0065] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.
[0066] Cyan toner dyes include CI Solvent Blue 70.
[0067] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.
[0068] The content of the colorant is preferably 0.1 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0069] <Wax> The toner of the present invention may contain wax, if necessary. Examples of the wax include the following.
[0070] Hydrocarbon waxes such as microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.
[0071] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene Saturated fatty acid bisamides such as bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0072] The content of the wax is preferably 2.0 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0073] <Charge control agent> The toner of the present invention may contain a charge control agent as necessary. Known charge control agents may be used as the charge control agent contained in the toner, but metal compounds of aromatic carboxylic acids are particularly preferred because they are colorless, can charge the toner quickly, and can stably maintain a constant charge amount.
[0074] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes. The charge control agent may be added internally or externally to the toner particles.
[0075] The amount of the charge control agent added is preferably 0.2 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0076] <Inorganic fine powder> The toner of the present invention may also contain other inorganic fine powders as necessary. The inorganic fine powders may be added internally to the toner particles, or may be mixed with the toner base particles as an external additive. As the external additive, inorganic fine powders such as silica are preferred. The inorganic fine powders are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0077] As an external additive to improve fluidity, 2 / g or more 400m 2 / g or less is preferable. In order to simultaneously improve fluidity and stabilize durability, inorganic fine particles having a specific surface area in the above range may be used in combination. The inorganic fine powder is preferably used in an amount of 0.1 parts by mass or more and 10.0 parts by mass or less per 100 parts by mass of toner particles. If the above range is satisfied, the effect of charge stability is easily obtained.
[0078] <Developer> The toner of the present invention can be used as a one-component developer, but in order to further improve dot reproducibility, it is preferable to mix it with a magnetic carrier and use it as a two-component developer, in that stable images can be obtained over a long period of time. That is, it is preferable that the toner is the toner of the present invention, which is a two-component developer containing a toner and a magnetic carrier.
[0079] Examples of magnetic carriers that can be used include generally known magnetic carriers such as iron powder with an oxidized surface, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.
[0080] When the toner is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio, in terms of the toner concentration in the two-component developer, is preferably 2% by mass or more and 15% by mass or less, and more preferably 4% by mass or more and 13% by mass or less.
[0081] <Method of manufacturing toner particles and method of manufacturing toner> The method for producing the toner particles is not particularly limited, and any of the conventionally known production methods such as suspension polymerization, emulsion aggregation, melt kneading, and dissolution suspension methods can be used.
[0082] The obtained toner particles may be mixed with the above-mentioned external additive fine particles according to the present invention, and other external additives as necessary, to obtain a toner. The toner particles, the above-mentioned external additive fine particles, and other external additives may be mixed using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation).
[0083] (Heat treatment process) In order to control the adhesion rate of the organosilicon compound fine particles to the toner particles by the water washing method described later, it is preferable to mix the organosilicon compound fine particles with the toner particles to obtain a toner particle mixture and then carry out a heat treatment.
[0084] That is, the toner manufacturing method preferably includes a mixing step of mixing toner particles and organosilicon compound fine particles to obtain a toner particle mixture, and a heat treatment step of heat-treating the toner particle mixture. By carrying out the heat treatment step, the adhesion rate of the organosilicon compound fine particles can be improved. The adhesion rate of the organosilicon compound fine particles to the toner particles (adhesion rate of the organosilicon compound fine particles by the water washing method) is preferably 50% or more. When the adhesion rate of the organosilicon compound fine particles is within the above range, even when a large amount of images are output over a long period of time, the organosilicon compound fine particles are unlikely to be detached from the toner, so that the charging stability is further improved. In addition, even when printing is performed for a long period of time under an environment in which the toner is excessively charged, such as a low humidity environment, the fine particles are unlikely to be detached from the toner, so that the effect of improving the charging stability can be further obtained. Furthermore, it is more preferable that it is 70% or more. The upper limit of the adhesion rate is not particularly limited, but is preferably 99% or less, more preferably 95% or less. The adhesion rate of the organosilicon compound fine particles to the toner particles can be controlled by the hot air temperature in the heat treatment step.
[0085] In the heat treatment step, for example, heat treatment can be performed with hot air using a heat treatment device shown in Fig. 1. The heat treatment device has a treatment chamber 6 for heat-treating a toner particle mixture (a mixture of toner particles and organosilicon compound fine particles), a toner particle mixture supplying means for supplying the toner particle mixture to the treatment chamber 6, hot air supplying means 7 for supplying hot air for heat-treating the toner particle mixture supplied from the toner particle mixture supplying means, and a recovery means 10 for discharging and recovering the heat-treated toner particles outside the treatment chamber 6 from an outlet provided in the treatment chamber 6.
[0086] 1 further has a regulating means 9 as a cylindrical member, and the treatment chamber 6 has a cylindrical shape that covers the outer circumferential surface of the regulating means 9. The hot air supplying means 7 is provided on one end side of the cylindrical shape of the treatment chamber 6 so that the hot air flows while rotating inside the cylindrical treatment chamber 6. The toner particle mixture supplying means is composed of a plurality of supply pipes 5 provided on the outer periphery of the treatment chamber 6.
[0087] Furthermore, the discharge port provided in the treatment chamber 6 is provided on the outer periphery of the end of the treatment chamber 6 on the side opposite to the side where the hot air supplying means 7 is provided, so as to be on an extension of the rotation direction of the toner particle mixture. The heat treatment using the heat treatment device having the above-mentioned configuration will be described below.
[0088] The toner particle mixture supplied by the raw material constant-volume supplying means 1 is introduced into an introduction pipe 3, which is installed vertically to the raw material constant-volume supplying means 1, by compressed gas adjusted by compressed gas flow rate adjusting means 2. The mixture passing through the introduction pipe is uniformly dispersed by a conical protruding member 4 provided in the center of the raw material constant-volume supplying means 1, and is introduced into eight supply pipes 5 that radiate outward, and then into a processing chamber 6 where heat treatment is carried out.
[0089] At this time, the flow of the mixture supplied to the processing chamber 6 is regulated by a regulating means 9 for regulating the flow of the mixture provided in the processing chamber 6. Therefore, the mixture supplied to the processing chamber is heat-treated while swirling in the processing chamber 6, and then cooled.
[0090] Heat for heat-treating the supplied mixture is supplied from hot air supplying means 7, distributed by distribution member 12, and introduced into treatment chamber 6 by swirling member 13 for swirling the hot air in a spiral shape. In terms of configuration, swirling member 13 for swirling the hot air has multiple blades, and the swirling of the hot air can be controlled by the number and angle of the blades. Hot air is supplied from hot air supplying means outlet 11.
[0091] The heat-treated toner particles are cooled by cold air supplied from cold air supplying means 8 (cold air supplying means 8-1, 8-2 and 8-3).
[0092] Next, the cooled toner particles are collected by the collecting means 10 at the bottom end of the processing chamber. A blower (not shown) is provided ahead of the collecting means, so that the toner particles are sucked and transported by the blower.
[0093] The powder particle supply port 14 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 10 of the thermal sphering treatment device is provided on the outer periphery of the treatment chamber so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 8 is configured to be supplied horizontally and tangentially from the outer periphery of the device to the circumferential surface inside the treatment chamber.
[0094] After obtaining the heat-treated toner particles, the heat-treated toner particles may be mixed with various external additives. The mixing device may be a double cone mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), a Nobilta (manufactured by Hosokawa Micron Corporation), or the like.
[0095] [Measurement methods for various physical properties] The methods for measuring various physical properties are described below.
[0096] <Separation of external additive particles and toner particles from toner> The inorganic fine particles can also be separated from the toner and measured by the following method.
[0097] Add 200 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1 g of toner to this dispersion and break up the toner clumps with a spatula or the like.
[0098] The centrifuge tube is shaken for 20 minutes at 350 reciprocations per minute using the shaker. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 3500 rpm for 30 minutes using a centrifuge. After centrifugation, the toner is present in the top layer in the glass tube, and inorganic fine particles are present in the aqueous solution in the lower layer. The aqueous solution in the lower layer is sampled and centrifuged to separate the sucrose and inorganic fine particles, and the inorganic fine particles are collected. Centrifugation is repeated as necessary to thoroughly separate the dispersion, and then the dispersion is dried and the inorganic fine particles are collected.
[0099] When a plurality of inorganic fine particles are added, the fine particles of the present invention can be selected by utilizing a centrifugal separation method or the like.
[0100] <Method for measuring adhesion rate of external additives by water washing method> The method for measuring the adhesion rate of external additives is as follows. First, the amount of external additives contained in the toner before the water washing process is quantified. The Si element intensity in the toner is measured using a wavelength dispersive X-ray fluorescence analyzer Axios advanced (manufactured by PANalytical). Next, the Si element intensity in the toner after the water washing process is measured in the same manner. The adhesion rate (%) can be calculated using the following formula. Adhesion rate (%)=(Si element intensity in toner after water washing treatment / Si element intensity in toner before water washing treatment)×100
[0101] <Method for measuring number-average particle size of external additives> The toner particles are observed with a scanning electron microscope (SEM) and the number and particle diameter (maximum diameter) of the organosilicon compound fine particles and titanic acid compound fine particles present on the surface of the toner particles are measured and determined. At this time, it is possible to confirm that the objects being measured are organosilicon compound fine particles or titanic acid compound fine particles by using an energy dispersive X-ray analyzer (EDS) attached to the SEM. The number-average particle diameter is the average value measured for 100 toner particles.
[0102] <Method for measuring the average circularity of external additives> The organosilicon compound microparticles and titanate compound microparticles are photographed using a scanning electron microscope (SEM) at a magnification of 25,000x and a pixel count of 1,280 x 960 (the size of one pixel is approximately 4 nm x 4 nm). The captured images are then analyzed using the image analysis software Image J (available from https: / / imagej.nih.gov / ij / ) to determine the circularity.
[0103] First, the contour of the organosilicon compound fine particle or titanic acid compound fine particle is extracted, and the projected area S and its perimeter L are measured.
[0104] Next, the equivalent circle diameter and circularity are calculated using the above area S and perimeter L. The equivalent circle diameter is the diameter of a circle having the same area as the projected area of the particle image, and the circularity is defined as the perimeter of the circle calculated from the equivalent circle diameter divided by the perimeter of the projected particle image, and is calculated using the following formula. Circularity = 2 × (π × S) 1 / 2 / L
[0105] The above circularity is calculated for at least 100 fine particles, and the arithmetic mean value is regarded as the average circularity of the organosilicon compound fine particles or titanic acid compound fine particles.
[0106] <Method for measuring the acid value of binder resin> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid components such as free fatty acids and resin acids contained in 1 g of a sample. The acid value is measured in accordance with JIS-K0070-1992 as follows.
[0107] (1) Reagents Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution.
[0108] Dissolve 7 g of special grade potassium hydroxide in 5 mL of water, and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide and leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is determined by placing 25 mL of 0.1 mol / L hydrochloric acid in an Erlenmeyer flask, adding several drops of the phenolphthalein solution, and titrating with the potassium hydroxide solution, and then calculating the amount of potassium hydroxide solution required for neutralization. The 0.1 mol / L hydrochloric acid used is prepared in accordance with JIS K 8001-1998.
[0109] (2) Operation (A) Main Test 2.0 g of the crushed sample is accurately weighed into a 200 mL Erlenmeyer flask, and 100 mL of a toluene / ethanol (2:1) mixed solution is added and dissolved for 5 hours. Next, several drops of the phenolphthalein solution are added as an indicator, and the potassium hydroxide solution is used for titration. The end point of the titration is when the indicator remains a light red color for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used).
[0110] (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (mL), C is the amount of potassium hydroxide solution added for the main test (mL), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).
[0111] <Method for measuring the acid value of polyester resin from toner> The acid value of the polyester resin from the toner can be measured by the following method: The polyester resin is separated from the toner by the following method, and the acid value is measured.
[0112] The toner is dissolved in tetrahydrofuran (THF), and the solvent is removed from the resulting soluble matter by distillation under reduced pressure to obtain a tetrahydrofuran (THF) soluble component of the toner.
[0113] The tetrahydrofuran (THF) soluble component of the obtained toner is dissolved in chloroform to prepare a sample solution having a concentration of 25 mg / ml.
[0114] 3.5 ml of the obtained sample solution is poured into the following apparatus, and resin components with molecular weights of 2000 or more are separated under the following conditions. Preparative GPC device: Preparative HPLC LC-980 model manufactured by Japan Analytical Industry Co., Ltd. Preparative column: JAIGEL 3H, JAIGEL 5H (manufactured by Japan Analytical Industry Co., Ltd.) Eluent: Chloroform Flow rate: 3.5ml / min After separating out the high molecular weight components derived from the resin, the solvent is distilled off under reduced pressure, and the mixture is dried for 24 hours under reduced pressure at 90°C. The above operation is repeated until about 2.0 g of the resin component is obtained. The acid value of the obtained sample is measured according to the above procedure.
[0115] <Method of measuring weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), and the measurement data is analyzed and calculated.
[0116] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).
[0117] Before carrying out the measurements and analyses, the dedicated software is set up as follows.
[0118] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.
[0119] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0120] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) Approximately 30 ml of the above-mentioned aqueous electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A predetermined amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolytic solution (5) in which the toner is dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).
[0121] <Solid 29 Method for measuring the abundance ratio of constituent compounds in organosilicon compound microparticles and SB / SA using Si-NMR> solid 29 In Si-NMR, peaks are detected in different shift regions depending on the structure of the functional group that bonds to the Si of the constituent compounds of the toner additive. By identifying the position of each peak using a standard sample, the structure that bonds to the Si can be identified. In addition, the abundance ratio of each constituent compound can be calculated from the obtained peak area. The ratio of the peak area of the Q unit structure, T unit structure, and D unit structure to the total peak area can be calculated.
[0122] solid 29 Specifically, the Si-NMR measurement conditions are as follows: Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: DDMAS method 29 Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 180s Scan:2000
[0123] After the measurement, the peaks of multiple silane components having different substituents and bonding groups of the sample or organosilicon compound microparticles are separated into the following M unit structures, D unit structures, T unit structures, and Q unit structures by curve fitting, and the peak areas of each are calculated.
[0124] Curve fitting is performed using EXcalibur for Windows (registered trademark) version 4.2 (EX series), software for JNM-EX400 manufactured by JEOL Ltd. Click "1D Pro" from the menu icon to load the measurement data. Next, select "Curve fitting function" from "Command" on the menu bar to perform curve fitting. Curve fitting is performed for each component so that the difference (composite peak difference) between the composite peak obtained by combining each peak obtained by curve fitting and the peak of the measurement result is minimized. M unit structure: (Ra)(Rb)(Rc)SiO 1 / 2 (S1) D unit structure: (Rd)(Re)Si(O 1 / 2 )2(S2) T unit structure: RfSi(O 1 / 2 )3(S3) Q unit structure: Si(O 1 / 2 )4(S4) Let (S1+S2+S3+S4)=SA.
[0125] In the formulae (S1), (S2) and (S3), Ra, Rb, Rc, Rd, Re and Rf each represent an organic group such as a hydrocarbon group having 1 to 6 carbon atoms (e.g., an alkyl group) or a halogen atom bonded to silicon. 29 Along with the Si-NMR measurement results 13 C-NMR and 1 The results of H-NMR may also be used to identify the compound. S2 / SA, S3 / SA, and S4 / SA are calculated from SA, S2, S3, and S4 thus determined.
[0126] (SB / SA calculation method) solid 29 From the chart obtained by Si-NMR, the peak area of (Si-R1) in each unit structure at the following position is calculated. R1 is, as described above, an alkyl group having 1 to 6 carbon atoms.
[0127] The peak area of (Si-R1) in the Q4 unit structure is S44, the peak area of (Si-R1) in the Q3 unit structure is S43, the peak area of (Si-R1) in the Q2 unit structure is S42, and the peak area of (Si-R1) in the Q1 unit structure is S41.
[0128] The peak area of (Si-R1) in the T3 unit structure is S33, the peak area of (Si-R1) in the T2 unit structure is S32, and the peak area of (Si-R1) in the T1 unit structure is S31.
[0129] The peak area of (Si-R1) in the D2 unit structure is S22, and the peak area of (Si-R1) in the D1 unit structure is S21.
[0130] The peak area of (Si-R1) in the M1 unit structure is designated as S11. At this time, the peak area ratio of Si-R1 in each unit structure is calculated as follows.
[0131] Peak area ratio of Si-R1 attributed to Q unit structure QB = (S44 / S4) x 0 + (S43 / S4) x 0 + (S42 / S4) x 0 + (S41 / S4) x 0 Peak area ratio of Si-R1 attributed to T unit structure TB = (S33 / S3) × 1 / 4 + (S32 / S3) × 1 / 4 + (S31 / S3) × 1 / 4 Peak area ratio of Si-R1 attributed to D unit structure DB = (S22 / S2) × 1 / 2 + (S21 / S2) × 1 / 2 Peak area ratio of Si-R1 attributed to M unit structure MB = S11 × 3 / 4 Q unit structure Q4: -105ppm~-115ppm Q3: -95ppm~-104ppm Q2:-85ppm~-94ppm Q1:-75ppm~-84ppm T unit structure T3: -60ppm~-70ppm T2: -50ppm~-59ppm T1: -40ppm~-49ppm D unit structure D2: -15ppm~-25ppm D1: -10ppm~14ppm M unit structure M1: -5ppm~-9ppm
[0132] Using the above formula, calculate SB / SA=QB+TB+DB+MB.
[0133] <Method of measuring surface treatment agent for organosilicon compound fine particles and titanic acid compound fine particles> The surface treatment agents for the organosilicon compound particles and the titanic acid compound particles are analyzed by pyrolysis GC-MS (gas chromatography mass spectrometry).
[0134] Specifically, the measurement conditions are as follows. Equipment: GC6890A (Agilent), pyrolysis equipment (Japan Analytical Industry Co., Ltd.) Column: HP-5ms 30m Thermal decomposition temperature: 590℃
[0135] The position of each peak in the profile obtained by measurement is identified using a standard sample, thereby identifying the surface treatment agent for the organosilicon compound fine particles and the titanic acid compound fine particles.
[0136] <Method for measuring the dielectric constant of fine particle B> Using a 284A precision LCR meter (manufactured by Hewlett-Packard), after calibration at frequencies of 1 kHz and 1 MHz, the complex dielectric constant at a frequency of 2 kHz is measured. 2 ) for 5 minutes to mold into a disk-shaped measurement sample with a diameter of 25 mm and a thickness of 1 mm or less (preferably 0.5 to 0.9 mm). This measurement sample is attached to an ARES (manufactured by Rheometric Scientific F.E.) equipped with a 25 mm diameter dielectric constant measurement jig (electrode), and measured at a frequency of 2 kHz under a load of 0.49 N (50 g) in an atmosphere at 25°C.
[0137] [Configuration included in the embodiment of the present invention] The disclosure of this embodiment includes the following configuration. (Configuration 1) A toner comprising toner particles containing a binder resin, fine particles A which are organosilicon compounds having siloxane bonds, and fine particles B, The fine particles A 29 In a chart obtained by Si-NMR measurement, when the total peak area attributable to the silicon polymer is SA and the peak area attributable to the Si-R1 bond (R1 represents an alkyl group having 1 to 6 carbon atoms) is SB, the following formula (1) is satisfied: 0.26≦SB / SA≦0.45 (1) The toner is characterized in that the fine particles B are a titanate compound, the average circularity of the primary particles of the fine particles B is 0.700 or more and 0.920 or less, and the ratio AD / BD of the number average particle diameter (AD) of the primary particles of the fine particles A to the number average particle diameter (BD) of the primary particles of the fine particles B satisfies the following formula: 1.0≦AD / BD≦10.0 (Configuration 2) The toner according to Configuration 1, wherein the number average particle diameter of the primary particles of the fine particles A is 0.02 μm or more and 0.30 μm or less. (Configuration 3) The toner according to configuration 1 or 2, wherein the fine particles A are surface-treated with at least one compound selected from the group consisting of alkylsilazane compounds, alkylalkoxysilane compounds, chlorosilane compounds, siloxane compounds, and silicone oils. (Configuration 4) The toner according to any one of Configurations 1 to 3, wherein the amount of the fine particles A added is X parts by mass and the amount of the fine particles B added is Y parts by mass relative to 100 parts by mass of the toner particles, and the following formula is satisfied: 0.7≦X / Y≦3.0 (Configuration 5) The toner according to any one of Configurations 1 to 4, wherein the content of the fine particles A is from 0.1 parts by mass to 20.0 parts by mass with respect to 100 parts by mass of the toner particles. (Configuration 6) The toner according to any one of Configurations 1 to 5, wherein the adhesion rate of the fine particles A to the toner particles is 50% or more and 99% or less. (Configuration 7) The toner according to any one of Configurations 1 to 6, wherein the fine particles B are strontium titanate. (Configuration 8) The toner according to any one of Configurations 1 to 7, wherein the number average particle diameter of the primary particles of the fine particles B is 0.01 μm or more and 0.10 μm or less. (Configuration 9) The toner according to any one of Configurations 1 to 8, wherein the fine particles B have a dielectric constant at 2 kHz of 10 pF / m or more and 40 pF / m or less. (Configuration 10) The toner according to any one of Configurations 1 to 9, wherein the fine particles B have a surface on which a compound having an alkyl group is present. (Configuration 11) The fine particles A 29 The toner according to any one of configurations 1 to 10, wherein in a chart obtained by Si-NMR measurement, when the total peak area attributable to the silicon polymer is SA, the peak area attributable to the Q unit structure is S4, the peak area attributable to the T unit structure is S3, and the peak area attributable to the D unit structure is S2, satisfies the following formulas (I) to (III): 0.20≦S4 / SA≦0.60 (I) 0≦S3 / SA≦0.50 (II) 0.20≦S2 / SA≦0.70 (III) EXAMPLES
[0138] The present invention will be described in more detail with reference to the following examples. However, these examples are not intended to limit the present invention in any way. In the following formulations, "parts" are all by weight unless otherwise specified.
[0139] <Production Example of Organosilicon Compound Fine Particles 1> 1. Hydrolysis process 43.2 g of RO water and 0.008 g of acetic acid as a catalyst were charged into a 200 ml beaker and stirred at 30° C. 32.6 g of tetraethoxysilane and 21.8 g of dimethyldimethoxysilane were added thereto and stirred for 0.5 hours to obtain a raw material solution.
[0140] 2. Polycondensation process 300.0g of methanol and 4.0g of 25% aqueous ammonia were added to a 1000ml beaker and stirred at 30°C to prepare an alkaline aqueous medium. The raw material solution obtained in 1. Hydrolysis step was added dropwise to this alkaline aqueous medium over 1 minute. The mixture after the dropwise addition of the raw material solution was stirred for 2.0 hours while keeping it at 30°C to allow the polycondensation reaction to proceed, and a polycondensation reaction liquid was obtained.
[0141] 3.Particleization process 250.0g of RO water was placed in a 2000ml beaker, and while stirring at 25℃, the polycondensation reaction liquid obtained in 2. Polycondensation step was added dropwise over 10 minutes. As soon as the polycondensation reaction liquid was mixed with the water, it became cloudy, and a dispersion liquid containing organosilicon compound particles having siloxane bonds was obtained. This dispersion liquid was stirred at 60℃ for 3.0 hours.
[0142] 4. Hydrophobization process 27.1 g of hexamethyldisilazane was added as a hydrophobizing agent to the dispersion liquid containing the organosilicon compound fine particles obtained in the above 3. Granulation step, and the mixture was stirred at 60°C for 3.0 hours. After leaving the mixture to stand for 5 minutes, the powder that precipitated at the bottom of the solution was collected by suction filtration and dried under reduced pressure at 120°C for 24 hours to obtain organosilicon compound fine particles 1. The number average particle size of the primary particle size of the obtained organosilicon compound fine particles 1 was 0.12 μm. The physical properties of organosilicon compound fine particles 1 are shown in Table 1.
[0143] <Production Example of Organosilicon Compound Fine Particles 2> In the hydrolysis step, the amounts of tetraethoxysilane and dimethyldimethoxysilane were changed to 16.9 g and 18.6 g, respectively, and 18.9 g of trimethoxymethylsilane was added, and the stirring temperature was changed to 30° C. and the stirring time to 0.5 hours, respectively. Except for this, organosilicon compound fine particles 2 were obtained in the same manner as in the production example of organosilicon compound fine particles 1. The physical properties of the obtained toner external additive particles 2 are shown in Table 1.
[0144] <Production Example of Organosilicon Compound Fine Particles 3> Organosilicon compound microparticles 3 were obtained in the same manner as in the production example of organosilicon compound microparticles 2, except that tetraethoxysilane was not added, trimethoxymethylsilane was changed to 45.2 g, and dimethyldimethoxysilane was changed to 9.2 g in the production example of organosilicon compound microparticles 2. The physical properties of the obtained organosilicon compound microparticles 3 are shown in Table 1.
[0145] <Production Example of Organosilicon Compound Fine Particles 4> Except for changing the hydrophobizing agent used in the hydrophobizing step to octamethylcyclotetrasiloxane, the same procedure as in the production example of organosilicon compound fine particles 1 was followed to obtain organosilicon compound fine particles 4. The physical properties of the obtained organosilicon compound fine particles 4 are shown in Table 1.
[0146] <Production Example of Organosilicon Compound Fine Particles 5> Except for changing the hydrophobizing agent used in the hydrophobizing step to chlorotrimethylsilane, the same procedure as in the production example of organosilicon compound fine particles 1 was followed to obtain organosilicon compound fine particles 5. The physical properties of the obtained organosilicon compound fine particles 5 are shown in Table 1.
[0147] <Production Example of Organosilicon Compound Fine Particles 6> Except for changing the hydrophobizing agent used in the hydrophobizing step to trifluoropropyltrimethoxysilane, the same procedure as in the production example of organosilicon compound fine particles 1 was followed to obtain organosilicon compound fine particles 6. The physical properties of the obtained organosilicon compound fine particles 6 are shown in Table 1.
[0148] <Production Example of Organosilicon Compound Fine Particles 7> Except for not adding a hydrophobizing agent in the hydrophobizing step, the same procedure as in the production example of organosilicon compound fine particles 1 was carried out to obtain organosilicon compound fine particles 7. The physical properties of the obtained organosilicon compound fine particles 7 are shown in Table 1.
[0149] <Production Example of Organosilicon Compound Fine Particle 8> Except for changing the stirring temperature to 40° C. and the stirring time to 1.0 hour in the hydrolysis step, the same procedure as in the production example of organosilicon compound fine particles 1 was carried out to obtain organosilicon compound fine particles 8. The physical properties of the obtained organosilicon compound fine particles 8 are shown in Table 1.
[0150] <Production Example of Organosilicon Compound Fine Particles 9> Except for changing the amount of 25% ammonia water used in the condensation polymerization step to 5.0 g, the same procedure as in the production example of organosilicon compound fine particles 1 was followed to obtain organosilicon compound fine particles 9. The physical properties of the obtained organosilicon compound fine particles 9 are shown in Table 1.
[0151] <Production Example of Organosilicon Compound Fine Particles 10> Except for changing the stirring temperature to 50° C. and the stirring time to 1.5 hours in the hydrolysis step, the same procedure as in the production example of organosilicon compound fine particles 1 was carried out to obtain organosilicon compound fine particles 10. The physical properties of the obtained organosilicon compound fine particles 10 are shown in Table 1.
[0152] <Production Example of Organosilicon Compound Fine Particles 11> Except for changing the amount of 25% ammonia water used in the polycondensation step to 6.0 g and changing the stirring time to 3.0 hours, the same procedure as in the production example of organosilicon compound microparticles 1 was followed to obtain organosilicon compound microparticles 11. The physical properties of the obtained organosilicon compound microparticles 11 are shown in Table 1.
[0153] <Production Example of Organosilicon Compound Fine Particles 12> Except for adding 54.4 g of trimethoxymethylsilane instead of tetraethoxysilane and dimethyldimethoxysilane in the hydrolysis step, organosilicon compound microparticles 12 were obtained in the same manner as in the production example of organosilicon compound microparticles 1. The physical properties of the obtained organosilicon compound microparticles 12 are shown in Table 1.
[0154] [Table 1]
[0155] <Production Example of Titanic Acid Compound Fine Particles 1> The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 50 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion.
[0156] A strontium chloride aqueous solution having a molar amount of 1.3 times the titania sol dispersion (2.2 moles, calculated as titanium oxide) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 1.1 moles / L.
[0157] Next, the mixture was stirred and heated to 90°C, and then 440mL of 10N sodium hydroxide solution was added over 15 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. After the reaction, pure water at 5°C was added to the slurry, which was then rapidly cooled to 30°C or less, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution at pH 5.0 was added to the slurry, which was stirred for 1 hour to dissolve and remove strontium carbonate, and the mixture was repeatedly washed with pure water.
[0158] Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 7.0 mass% of isobutyltrimethoxysilane was added based on the solid content of the slurry, and the mixture was stirred for 10 hours. The mixture was then neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain titanic acid compound microparticles 1. The physical properties of the obtained titanic acid compound microparticles 1 are shown in Table 2.
[0159] <Production Example of Titanic Acid Compound Fine Particles 2> Titanate compound fine particles 2 were obtained in the same manner as in the production example of titanate compound fine particles 1, except that isobutyltrimethoxysilane was not added in the production example of titanate compound fine particles 1. The physical properties of the obtained titanate compound fine particles 2 are shown in Table 2.
[0160] <Production Example of Titanic Acid Compound Fine Particles 3> The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 50 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion.
[0161] A strontium chloride aqueous solution having a molar amount of 1.2 times the amount of the titania sol dispersion (2.6 moles, calculated as titanium oxide) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 1.3 moles / L.
[0162] Next, the mixture was stirred and heated to 95°C, and then 312 mL of 15N sodium hydroxide solution was added over 5 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. After the reaction, pure water at 5°C was added to the slurry, which was then rapidly cooled to 30°C or less, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution at pH 5.0 was added to the slurry, which was stirred for 1 hour to dissolve and remove strontium carbonate, and the mixture was repeatedly washed with pure water.
[0163] Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 5.0 mass% of isobutyltrimethoxysilane was added based on the solid content of the slurry, and the mixture was stirred for 10 hours. The mixture was then neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain titanic acid compound microparticles 3. The physical properties of the obtained titanic acid compound microparticles 3 are shown in Table 2.
[0164] <Production Example of Titanic Acid Compound Fine Particles 4> The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 100 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion.
[0165] The titania sol dispersion was mixed with 1.0 times the molar amount of an aqueous strontium chloride solution relative to 0.6 moles (equivalent to titanium oxide) of the titania sol dispersion, and the mixture was placed in a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 0.3 moles / L.
[0166] Next, the mixture was stirred and heated to 70°C, after which 750mL of 2N sodium hydroxide solution was added over 120 minutes, and the reaction was carried out for 20 minutes. The slurry after the reaction was gradually cooled to 30°C or less over 1 hour, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution of pH 5.0 was added to the slurry, and the mixture was stirred for 1 hour to dissolve and remove strontium carbonate, and then repeatedly washed with pure water.
[0167] Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 5.0 mass% of isobutyltrimethoxysilane was added based on the solid content of the slurry, and the mixture was stirred for 10 hours. The mixture was then neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain titanic acid compound microparticles 4. The physical properties of the obtained titanic acid compound microparticles 4 are shown in Table 2.
[0168] <Production Example of Titanic Acid Compound Fine Particles 5> The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 100 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion.
[0169] The titania sol dispersion was mixed with 1.0 times the molar amount of an aqueous strontium chloride solution relative to 0.6 moles (equivalent to titanium oxide) of the titania sol dispersion, and the mixture was placed in a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 0.3 moles / L.
[0170] Next, the mixture was stirred and heated to 70°C, after which 750mL of 2N sodium hydroxide solution was added over 120 minutes, and the reaction was carried out for 20 minutes. The slurry after the reaction was gradually cooled to 30°C or less over 1 hour, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution of pH 5.0 was added to the slurry, and the mixture was stirred for 1 hour to dissolve and remove strontium carbonate, and then repeatedly washed with pure water.
[0171] Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 5.0 mass% of isobutyltrimethoxysilane was added based on the solid content of the slurry, and the mixture was stirred for 10 hours. Then, the mixture was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain titanic acid compound microparticles 5. The physical properties of the obtained titanic acid compound microparticles 5 are shown in Table 2.
[0172] <Production Example of Titanic Acid Compound Fine Particles 6> Titanate compound fine particles 6 were obtained in the same manner as in the production example of titanate compound fine particles 1, except that strontium chloride was replaced with calcium chloride. The physical properties of the obtained titanate compound fine particles 6 are shown in Table 2.
[0173] <Production Example of Titanic Acid Compound Fine Particles 7> The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 50 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion.
[0174] A strontium chloride aqueous solution having a molar amount of 1.2 times the amount of the titania sol dispersion (2.0 moles, calculated as titanium oxide) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 1.0 mole / L.
[0175] Next, the mixture was stirred and heated to 85°C, and then 800mL of 5N sodium hydroxide solution was added over 20 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. The slurry after the reaction was gradually cooled to 30°C or less over 1 hour, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution of pH 5.0 was added to the slurry and stirred for 1 hour to dissolve and remove strontium carbonate, and then the mixture was repeatedly washed with pure water.
[0176] Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 30.0 mass% of isobutyltrimethoxysilane was added based on the solid content of the slurry, and the mixture was stirred for 10 hours. Then, the mixture was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain titanic acid compound microparticles 7. The physical properties of the obtained titanic acid compound microparticles 7 are shown in Table 2.
[0177] <Production Example of Titanic Acid Compound Fine Particles 8> The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 100 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion.
[0178] A strontium chloride aqueous solution having a molar amount of 1.1 times the titania sol dispersion (1.4 moles, calculated as titanium oxide) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 0.7 moles / L.
[0179] Next, the mixture was stirred and heated to 80°C, and then 500mL of 20N sodium hydroxide solution was added over 5 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. After the reaction, pure water at 5°C was added to the slurry, which was then rapidly cooled to 30°C or less, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution at pH 5.0 was added to the slurry, which was stirred for 1 hour to dissolve and remove strontium carbonate, and the mixture was repeatedly washed with pure water.
[0180] Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 2.0 mass% of isobutyltrimethoxysilane was added based on the solid content of the slurry, and the mixture was stirred for 10 hours. Then, the mixture was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain titanic acid compound microparticles 8. The physical properties of the obtained titanic acid compound microparticles 8 are shown in Table 2.
[0181] [Table 2]
[0182] <Production Example of Polyester Resin A1> 76.9 parts (0.167 moles) of polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane, 25 parts (0.145 moles) of terephthalic acid (TPA), 8.0 parts (0.054 moles) of adipic acid, and 0.5 parts of titanium tetrabutoxide were placed in a 4-liter 4-neck glass flask, and a thermometer, a stirring rod, a condenser, and a nitrogen inlet tube were attached and placed in a mantle heater. Next, the flask was substituted with nitrogen gas, and the temperature was gradually raised while stirring, and the mixture was reacted for 4 hours while stirring at a temperature of 200°C. (First reaction step) Then, 1.2 parts (0.006 moles) of trimellitic anhydride (TMA) was added, and the mixture was reacted at 180°C for 1 hour (second reaction step), to obtain binder resin 1. The acid value of this binder resin 1 was 5 mgKOH / g.
[0183] <Production Example of Polyester Resin A2> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane 71.3 parts (0.155 moles) Terephthalic acid 24.1 parts (0.145 moles) Titanium tetrabutoxide 0.6 parts The above materials were placed in a 4-liter glass four-neck flask, and a thermometer, a stirring rod, a condenser, and a nitrogen inlet tube were attached and placed in a mantle heater. Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the mixture was reacted for 2 hours while stirring at a temperature of 200°C. Then, 5.8 parts (0.030 mol%) of trimellitic anhydride was added, and the mixture was reacted at 180°C for 10 hours to obtain polyester resin A2. The acid value of this polyester resin A2 was 10 mgKOH / g.
[0184] <Production Example of Crystalline Polyester 1> In a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, 100.0 mol parts of 1,10-decanedicarboxylic acid as a carboxylic acid monomer and 100.0 mol parts of 1,6-hexanediol as an alcohol monomer were added. The mixture was heated to 140°C while stirring, and then heated to 140°C under a nitrogen atmosphere and reacted for 8 hours while distilling off water under normal pressure. Next, 0.57 parts of tin dioctyl acid was added to 100 parts of the combined carboxylic acid monomer and alcohol monomer, and the mixture was reacted while heating to 200°C at a rate of 10°C / hour. After the reaction was continued for 2 hours after reaching 200°C, the pressure in the reaction vessel was reduced to 5 kPa or less, and the mixture was reacted at 200°C while monitoring the molecular weight to obtain a crystalline polyester 1.
[0185] <Production Example of Toner Base Particle 1> Polyester resin A1 70.0 parts Polyester resin A2 30.0 parts Crystalline polyester 1 6.0 parts Fischer-Tropsch wax (maximum endothermic peak temperature 78°C) 5.0 parts CI Pigment Blue 15:3 5.0 parts The raw materials shown in the above recipe were mixed using a Henschel mixer (FM-75, Nippon Coke & Engineering Co., Ltd.) at a rotation speed of 20 s-1 for 5 minutes, and then kneaded in a twin-screw kneader (PCM-30, Ikegai Co., Ltd.) set at a temperature of 125°C and a rotation speed of 300 rpm. The kneaded product obtained was cooled and coarsely crushed to a diameter of 1 mm or less using a hammer mill to obtain a coarsely crushed product. The obtained coarsely crushed product was finely crushed using a mechanical grinder (T-250, Freund Turbo Co., Ltd.).
[0186] Further, classification was carried out using a rotary classifier (200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles 1. The operating conditions of the rotary classifier (200TSP, manufactured by Hosokawa Micron Corporation) were a classification rotor rotation speed of 50.0 s -1 The resulting toner base particles 1 had a weight average particle size (D4) of 5.9 μm.
[0187] <Toner 1 Manufacturing Example> Next, to the obtained toner base particles 1, the organosilicon compound fine particles 1 were externally added as a first external addition treatment as described below.
[0188] 100 parts of toner base particles Organosilicon compound fine particles 1 4.0 parts The above materials were mixed in a Henschel mixer FM-10C (manufactured by Nippon Coke and Kogyo Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at 100° C. for a rotation time of 10 minutes to obtain toner base particle mixture 1.
[0189] (Heat treatment process) The obtained toner base particle mixture 1 was subjected to a heat treatment by the surface treatment device shown in Fig. 1. The operating conditions for the heat treatment were feed rate = 2 kg / hr, hot air temperature = 150°C, and hot air flow rate = 6 m 3 / min, cold air temperature = -5℃, cold air flow rate = 2.5m 3 / min, Blower air volume = 11m 3 / min, injection air flow rate = 1m 3 / min.
[0190] Next, fine powder and coarse powder were simultaneously classified and removed using a wind classifier utilizing the Coanda effect ("Elbow Jet Lab EJ-L3", manufactured by Nittetsu Mining Co., Ltd.) to obtain toner particles 1. The obtained heat-treated toner particles 1 were subjected to a second external addition treatment as described below.
[0191] 100 parts of toner particles Organosilicon compound fine particles 1 2.0 parts Titanic acid compound fine particles 1 3.0 parts The above materials were mixed in a Henschel mixer (product name: FM-10C type, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 67 s. -1 After mixing at room temperature at a rotation speed of 4000 rpm for 2 minutes, the mixture was passed through an ultrasonic vibration sieve with a mesh size of 54 μm to obtain toner 1. The physical properties of toner 1 thus obtained are shown in Table 3.
[0192] <Production examples of toners 2 to 28> Toners 2 to 28 were obtained in the same manner as in the production example of toner 1, except that the types and amounts of organosilicon compound fine particles and titanic acid compound fine particles, whether or not a hot air treatment step was performed, and the hot air temperature in the heat treatment step were changed to those shown in Table 3. The physical properties of toners 2 to 28 are shown in Table 3.
[0193] [Table 3]
[0194] <Production example of carrier 1> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles.
[0195] Phenol: 10% by weight Formaldehyde solution: 6% by weight (40% by weight of formaldehyde, 10% by weight of methanol, 50% by weight of water) Magnetite treated with the above silane compound 1:58 mass% Magnetite treated with the above silane compound 2: 26% by mass 100 parts of the above material, 5 parts of 28% by mass aqueous ammonia, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and maintained at 85°C while stirring and mixing, and a polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain a spherical magnetic material-dispersed carrier 1. The 50% particle size (D50) based on volume was 34.2 μm.
[0196] <Production Example of Two-Component Developer 1> Toner 1 (8.0 parts) was added to carrier 1 (92.0 parts), and the mixture was mixed in a V-type mixer (V-20, manufactured by Seishin Enterprise Co., Ltd.) to obtain two-component developer 1.
[0197] <Production Examples of Two-Component Developers 2 to 28> Two-component developers 2 to 28 were obtained by carrying out production in the same manner as in the production example of two-component developer 1, except that the toner was changed as shown in Table 4.
[0198] [Table 4]
[0199] <Toner Evaluation Method> The two-component developers 1 to 28 were used to carry out the following evaluations.
[0200] The image forming device used was the imagePRESS C850 (Canon), with the development contrast adjustable to any value and the automatic correction by the device disabled. The copy speed was 85 sheets / min (A4 paper). The frequency of the alternating electric field was fixed at 2.0 kHz, and the peak-to-peak voltage (Vpp) was adjustable from 0.7 kV to 1.8 kV in 0.1 kV increments.
[0201] A two-component developer was placed in the developing device at the cyan position of this image forming apparatus, and the charging voltage VD of the electrostatic latent image carrier and the laser power were adjusted to perform the evaluation described below. 2 ), Canon Marketing Japan Inc.) were used.
[0202] (1) Evaluation of developability before and after continuous printing In a normal temperature and low humidity environment (N / L; temperature 25° C., relative humidity 10%), the initial Vpp was fixed at 1.3 kV, and the contrast potential was set so that the reflection density of a cyan monochrome solid image was 1.50.
[0203] With these settings, an image pattern with a cyan monochromatic image ratio of 1% to the paper surface was output continuously on 5,000 sheets. After that, a cyan monochromatic solid image was output again with Vpp at 1.3 kV, and the reflection density was measured. The contrast potential at which the reflection density of the cyan monochromatic solid image was 1.50 was determined, and the difference from the initial value was compared. The reflection density was measured using a spectrodensitometer 500 series (manufactured by X-Rite). The evaluation results were ranked according to the following criteria. Rank D or higher was judged to be good. (Evaluation Criteria) A: The difference from the initial value is less than 35V. B: The difference from the initial value is between 35V and 60V. C: The difference from the initial value is between 60V and 80V. D: The difference from the initial value is between 80V and 100V. E: The difference from the initial value is 100V or more.
[0204] (2) Method for evaluating fogging on non-image areas (white areas) after durability test The amount of toner on the paper in the FFh image (solid image) was adjusted to 0.45 mg / cm2. The evaluation environments were a high temperature and high humidity environment (H / H; temperature 30°C, relative humidity 80%) and an N / L environment, and in each environment, a 1 cm x 1 cm FFh image was printed in the center of 50,000 sheets of A4 paper, and then fogging in the white background was measured.
[0205] The reflectance Dr (%) of the evaluation paper before image output was measured using a reflectometer (Tokyo Denshoku Co., Ltd.'s "REFLECTOMETER MODEL TC-6DS"). After durability (50,001st sheet), the reflectance Ds (%) of the 00H image area (white area) was measured. From the obtained Dr and Ds, the fog (%) was calculated using the following formula. Fog(%)=Dr(%)-Ds(%)
[0206] The evaluation results were ranked according to the following criteria. Rank D or higher was considered to be good. (Evaluation Criteria) A: Less than 1.0% B: 1.0% or more but less than 1.5% C: 1.5% or more and less than 2.0% D: 2.0% or more and less than 2.5% E: 2.5% or more
[0207] <Evaluation Results of Examples 1 to 22> Table 5 shows the evaluation results of Examples 1 to 22 using the two-component developers 1 to 22.
[0208] <Evaluation Results of Comparative Examples 1 to 6> Table 5 shows the evaluation results of Comparative Examples 1 to 6 using two-component developers 23 to 28.
[0209] [Table 5] [Explanation of symbols]
[0210] 1. raw material fixed quantity supply means, 2. compressed gas flow rate adjustment means, 3. introduction pipe, 4. protruding member, 5. supply pipe, 6. treatment chamber, 7. hot air supply means, 8. cold air supply means, 9. regulating means, 10. recovery means, 11. hot air supply means outlet, 12. distribution member, 13. swirling member, 14. powder particle supply port
Claims
1. A toner comprising toner particles containing a binder resin, fine particles A which are organosilicon compounds having siloxane bonds, and fine particles B, The fine particles A 29 In a chart obtained by Si-NMR measurement, when the total peak area attributable to the silicon polymer is defined as SA and the peak area attributable to the Si-R1 bond (R1 represents an alkyl group having 1 to 6 carbon atoms) is defined as SB, the following formula (1) is satisfied: 0.26≦SB / SA≦0.45 ... (1) The toner is characterized in that the fine particles B are a titanate compound, the average circularity of the primary particles of the fine particles B is 0.700 or more and 0.920 or less, and the ratio AD / BD of the number average particle diameter (AD) of the primary particles of the fine particles A to the number average particle diameter (BD) of the primary particles of the fine particles B satisfies the following formula: 1.0≦AD / BD≦10.0
2. 2. The toner according to claim 1, wherein the number average particle diameter of the primary particles of the fine particles A is 0.02 [mu]m or more and 0.30 [mu]m or less.
3. 3. The toner according to claim 1, wherein the fine particles A are surface-treated with at least one compound selected from the group consisting of alkylsilazane compounds, alkylalkoxysilane compounds, chlorosilane compounds, siloxane compounds, and silicone oils.
4. 3. The toner according to claim 1, wherein the amount of the fine particles A added is X parts by mass and the amount of the fine particles B added is Y parts by mass relative to 100 parts by mass of the toner particles, and the following formula is satisfied: 0.7≦X / Y≦3.0
5. 3. The toner according to claim 1, wherein the content of the fine particles A is from 0.1 parts by mass to 20.0 parts by mass with respect to 100 parts by mass of the toner particles.
6. 3. The toner according to claim 1, wherein the adhesion rate of the fine particles A to the toner particles is 50% or more and 99% or less.
7. 3. The toner according to claim 1, wherein the fine particles B are strontium titanate.
8. 3. The toner according to claim 1, wherein the number average particle diameter of the primary particles of the fine particles B is 0.01 [mu]m or more and 0.10 [mu]m or less.
9. 3. The toner according to claim 1, wherein the fine particles B have a dielectric constant of 10 pF / m or more and 40 pF / m or less at 2 kHz.
10. 3. The toner according to claim 1, wherein the fine particles B have a surface on which a compound having an alkyl group is present.
11. The fine particles A 29 The toner according to claim 1 or 2, wherein in a chart obtained by Si-NMR measurement, when the total peak area assigned to the silicon polymer is SA, the peak area assigned to the Q unit structure is S4, the peak area assigned to the T unit structure is S3, and the peak area assigned to the D unit structure is S2, the following formulas (I) to (III) are satisfied: 0.20≦S4 / SA≦0.60...(I) 0≦S3 / SA≦0.50...(II) 0.20≦S2 / SA≦0.70...(III)
Citation Information
Patent Citations
Sofer-bed assembly
JP1986016711A
Highly hydrophobic spherical sol-gel silica fine particle, method for producing the same, toner external additive for electrostatic charge image development composed of the fine particle, and developer using the toner external additive
JP2007099582A
toner
JP2022022414A